Impact of Intimate Partner Violence on Women's Labor Force Participation in Illinois, 1999-2002 - Riger, Stephanie ([Verlag nicht ermittelbar], 2012)
The first goal of this study was to identify the incidence of partner violence among Temporary Assistance for Needy Families (TANF) recipients over a three-year period. The second goal of this study was to examine the impact of partner violence on women's labor force participation over time. A final goal of this research was to explore the short and longer-term consequences of victimization on women's employment and economic well-being, as well as their physical and mental health. This study used the first three years of data from the Illinois Families Study (IFS). The first of the annual surveys was administered between November 1999 and September 2000, the second between February 2001 and September 2001, and the third between February 2002 and September 2002. The three data files contain very similar information including such items as a household roster, housing and neighborhood characteristics, employment, literacy and skills, parenting, and children. There is also information related to the respondent's history, health, self-efficacy, life events, experiences with domestic violence, civic participation and social support, income resources, and experiences with welfare. The Part 1 (Wave 1 Data) data file contains 1,323 cases and 942 variables. The Part 2 (Wave 2 Data) data file contains 1,183 cases and 763 variables. The Part 3 (Wave 3 Data) data file contains 1,072 cases and 778 variables. Additional information about the Illinois Families Study (IFS) is available on the IFS Web site.